Artificial Intelligence: The Game Changer in Scientific Research - Ilegbusi, Paul (My University, 2024)
Artificial Intelligence (AI) has revolutionised scientific research by enhancing data analysis, accelerating research processes, and improving accuracy. AI's applications span various fields, including biomedicine, environmental science, physics, and materials science. This paper explores AI's transformative impact on scientific research, highlighting its role, applications, challenges, and future prospects. AI tools, such as Explain Paper, Paper Digest, and Chatdoc, facilitate research by summarizing papers, explaining complex concepts, and assisting with literature reviews. Despite AI's benefits, challenges persist, including data privacy and security concerns, bias, and transparency issues. To address these challenges, the paper emphasizes the need for ethical guidelines, robust security measures, and interpretable AI models. The future of AI in scientific research holds promise, with emerging trends and technologies, interdisciplinary innovations, and collaborative platforms driving progress. The paper concludes by highlighting the importance of addressing AI's challenges to ensure its beneficial impact on science and society.
An Artificial Intelligence Seminar paper.
Keywords: Artificial Intelligence